2004
DOI: 10.1038/nature02677
|View full text |Cite
|
Sign up to set email alerts
|

PTK7/CCK-4 is a novel regulator of planar cell polarity in vertebrates

Abstract: In addition to the apical-basal polarity pathway operating in epithelial cells, a planar cell polarity (PCP) pathway establishes polarity within the plane of epithelial tissues and is conserved from Drosophila to mammals. In Drosophila, a 'core' group of PCP genes including frizzled (fz), flamingo/starry night, dishevelled (dsh), Van Gogh/strabismus and prickle, function to regulate wing hair, bristle and ommatidial polarity. In vertebrates, the PCP pathway regulates convergent extension movements and neural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
510
4
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(535 citation statements)
references
References 23 publications
17
510
4
4
Order By: Relevance
“…At the 50% level, OHC3 has 61% misalignment, while OHC2 and 1 have 36% and 12%, respectively, and the IHC layer has only 11%. This pattern is more similar to that seen in PCP mutants such as circletail (Scrib1), and PTK7 (Montcouquiol et al, 2003;Lu et al, 2004), where the OHC3 is predominantly affected and the IHC is relatively unaffected. Cecr2 and Ptk7 mutants show other similarities.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…At the 50% level, OHC3 has 61% misalignment, while OHC2 and 1 have 36% and 12%, respectively, and the IHC layer has only 11%. This pattern is more similar to that seen in PCP mutants such as circletail (Scrib1), and PTK7 (Montcouquiol et al, 2003;Lu et al, 2004), where the OHC3 is predominantly affected and the IHC is relatively unaffected. Cecr2 and Ptk7 mutants show other similarities.…”
Section: Discussionsupporting
confidence: 67%
“…A ''core'' set of PCP genes was established in Drosophila (Fanto and McNeill, 2004). Homologues in vertebrates include Vangl1/ 2, Frizzled3 and 6, Disheveled1-3, Celsr1, Prickle, Scribbled, PTK7, and Ankrd6 (Schwarz-Romond et al, 2002;Carreira-Barbosa et al, 2003;Curtin et al, 2003;Montcouquiol et al, 2003;Lu et al, 2004;Wang et al, 2006a,b;Torban et al, 2007). Examples of PCP can be observed throughout vertebrate embryogenesis, most notably in the convergent extension (CE) movements required to elongate and shape the neural epithelium during early neurulation, as well as the highly organized epithelium within the cochlear sensory structures (Park and Moon, 2002;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that there are orientation defects in Dvl1/2 (Dishevelled) double mu-tants (Wang et al, 2005), but the overall level of disruption appears mild in these animals and may be complicated by functional redundancy and additional roles for Dvl. Whereas the PCP functions of Vangl2 and Celsr1 seem to have been maintained between vertebrates and invertebrates, Scrb1 and PTK-7 are apparently novel vertebrate PCP genes that have no role in PCP in Drosophila (Montcouquiol et al, 2003;Lu et al, 2004). Together, these results and our data suggest that, although there has been an overall conservation of function in terms of the molecular pathways that generate PCP, significant differences probably exist between vertebrates and invertebrates.…”
Section: Introductionsupporting
confidence: 36%
“…Recent results have identified a group of mammalian PCP mutants that affect HC stereociliary bundle orientation, including Vangl2 (Van Gogh-like) Scrb1 (Scribble), Celsr1 (cadherin EGF LAG seven-pass G-type receptor), and protein tyrosine kinase-7 (PTK-7 ) (Curtin et al, 2003;Montcouquiol et al, 2003;Lu et al, 2004). It has also been reported that there are orientation defects in Dvl1/2 (Dishevelled) double mu-tants (Wang et al, 2005), but the overall level of disruption appears mild in these animals and may be complicated by functional redundancy and additional roles for Dvl.…”
Section: Introductionmentioning
confidence: 99%